Transformative Climate Finance : A New Approach for Climate Finance to Achieve Low-Carbon Resilient Development in Developing Countries - World Bank Group (World Bank, Washington, DC, 2020)
This report analyses options to make international public climate finance more transformative. The report identifies eight sets of levers to drive climate action: project-based investments, financial sector reform, fiscal policy, sectoral policies, trade policy, innovation and technology transfer, carbon markets, and climate intelligence. It then examines how climate finance is deployed to address barriers to action for each lever and derives general principles for transformative climate finance based on this analysis relating to allocation of climate finance, use of different financial instruments and other improvements in modalities and processes.